Early Endothelial Progenitor Cells (eEPCs) in systemic sclerosis (SSc) - dynamics of cellular regeneration and mesenchymal transdifferentiation. Issue 1 (December 2016) - Patschan, S.; Tampe, D.; Müller, C.; Seitz, C.; Herink, C.; Müller, G.; Zeisberg, E.; Zeisberg, M.; Henze, E.; Patschan, D.
Abstract Background Patients with systemic sclerosis (SSc) are endagered by tissue fibrosis and by microvasculopathy, with the latter caused by endothelial cell expansion/proliferation. SSc-associated fibrosis potentially results from mesenchymal transdifferentiation of endothelial cells. Early Endothelial Progenitor Cells (eEPCs) act proangiogenic under diverse conditions. Aim of the study was to analyze eEPC regeneration and mesenchymal transdifferentiation in patients with limited and diffuse SSs (lSSc and dSSc). Methods Patients with both, lSSc and dSSc were included into the study. The following parameters were evaluated: eEPC numbers and regeneration, concentrations of vasomodulatory mediators, mesenchymal properties of blood-derived eEPC. Serum samples of healthy subjects and SS patients were used for stimulation of cultured human eEPC, subsequently followed by analysis of mesenchymal cell characteristics and mobility. Results Twenty-nine patients were included into the study. Regenerative activity of blood-derived eEPCs did not differ between Controls and patients. Circulating eEPC were significantly lower in all patients with SSc, and in limited and diffuse SSc (lSSc/dSSc). Serum concentrations of promesenchymal TGF-b was elevated in all patients with SSc. Cultured mononuclear cells from SS patients displayed higher abundances of CD31 and of CD31 and aSMA combined. Finally, serum from SSc patients inhibited migration of cultured eEPCs and the cells showed lower sensitivity towards the endothelin antagonist Bosentan. Conclusions The eEPC system, which represents an essential element of the endogenous vascular repair machinery is affected in SSc. The increased appearance of mesenchymal properties in eEPC may indicate that alterations of the cells potentially contribute to the accumulation of connective tissue and to vascular malfunction.